1971
DOI: 10.1086/151178
|View full text |Cite
|
Sign up to set email alerts
|

Rocket Observations of the Ultraviolet Solar Spectrum during the Total Eclipse of 1970 March 7

Abstract: A sequence of thirty-five ultraviolet photographic spectra of the Sun has been obtained in the wavelength region 850-2190 Â, as a function of time during the eclipse. These cover the range from before second contact until midtotality, with a spatial resolution of the order 2 arc sec. A general description of the experiment and data is given. Twenty-five new coronal lines have been seen, the majority of which have been identified as new forbidden transitions. The La corona is observed out to over 1.5 Rq, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Many of the 2s 3 S2p 3 P transitions in Ne 8+ , Na 9+ , Mg 10+ , and Si 12+ have recently been observed in solar flare plasmas, in which also the wavelength of the Na X line at 111.177 nm could be measured for the first time (Curdt et al 2000). The corresponding O VII line had been tentatively identified at 162.4 nm in an early eclipse spectrum by Gabriel et al (1971). This identification was then confirmed using Skylab spectra by Feldman and Doschek (1977c).…”
Section: Flaresmentioning
confidence: 80%
“…Many of the 2s 3 S2p 3 P transitions in Ne 8+ , Na 9+ , Mg 10+ , and Si 12+ have recently been observed in solar flare plasmas, in which also the wavelength of the Na X line at 111.177 nm could be measured for the first time (Curdt et al 2000). The corresponding O VII line had been tentatively identified at 162.4 nm in an early eclipse spectrum by Gabriel et al (1971). This identification was then confirmed using Skylab spectra by Feldman and Doschek (1977c).…”
Section: Flaresmentioning
confidence: 80%
“…The emission of the Lα λ1216 line in the solar corona has been discovered by Gabriel et al (1971). They concluded that in most coronal structures the process responsible for the formation of the Lα line is the photo-excitation by underlying radiation.…”
Section: Expression Of the Stokes Parametersmentioning
confidence: 99%
“…At higher levels, and for bright enough exciting chromospheric radiation, lines form also via resonant scattering of radiation: this is the dominant process for the H  Lyα, while both components need to be considered for the O  lines. The Lyα line is produced by resonance scattering (Gabriel et al 1971) and is therefore subject to Doppler dimming (Hyder & Lites 1970). The two lines of the O  resonance doublet are excited in part by collisions with free electrons, in part by transition region radiation (Kohl & Withbroe 1982), therefore their radiative components can be affected by Doppler dimming.…”
Section: Density Estimatementioning
confidence: 99%